If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = lx + 3l + -1 Reorder the terms: y = -1 + 3l + lx Solving y = -1 + 3l + lx Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -1 + 3l + lx
| 3/16x4/9 | | 24+2x=3x+48 | | (X+7)-8=12 | | 2e^3x=30 | | 24x+2x=3x+48 | | 30X+60-30X=60 | | 30X+30-30X=60 | | X2=36/64 | | 6(7-5x)-5x=252 | | 6x-14=6x+14 | | 11=s/2 | | 4x^3+12x^2+6x-2=0 | | 5=d/8 | | 0.1666666= | | (2n+6)4=-2n+4 | | =X/2*2× | | X/2*2× | | 34=-1/4y | | -4x=-31 | | (X+4)(3x-2)=3x(x+1) | | 42=2/5x-7 | | X-24=3x | | 100=y-16 | | 4(2+5)-3z=5 | | 13(p+2)=-30 | | -x-8=2-3x | | 3x^2-2x+12x-8=3x^2+3x | | 4x+7y=107 | | e^2-7x=834 | | -10-5x^2=-510 | | 7-2x=3-2(x-2) | | X/11=13/8 |